Ydj1 governs fungal morphogenesis and stress response, and facilitates mitochondrial protein import via Mas1 and Mas2 - Jinglin L. Xie; Iryna Bohovych; Erin O.Y. Wong; Jean-Philippe Lambert; Anne-Claude Gingras; Oleh Khalimonchuk; Leah E. Cowen; Michelle D. Leach (Microbial Cell)
Mitochondria underpin metabolism, bioenergetics, signalling, development and cell death in eukaryotes. Most of the ~1,000 yeast mitochondrial proteins are encoded in the nucleus and synthesised as precursors in the cytosol, with mitochondrial import facilitated by molecular chaperones. Here, we focus on the Hsp40 chaperone Ydj1 in the fungal pathogen Candida albicans, finding that it is localised to both the cytosol and outer mitochondrial membrane, and is required for cellular stress responses and for filamentation, a key virulence trait. Mapping the Ydj1 protein interaction network highlighted connections with co-chaperones and regulators of filamentation. Furthermore, the mitochondrial processing peptidases Mas1 and Mas2 were highly enriched for interaction with Ydj1. Additional analysis demonstrated that loss of MAS1, MAS2 or YDJ1 perturbs mitochondrial morphology and function. Deletion of YDJ1 impairs import of Su9, a protein that is cleaved to a mature form by Mas1 and Mas2. Thus, we highlight a novel role for Ydj1 in cellular morphogenesis, stress responses, and mitochondrial import in the fungal kingdom.